Kesadaran Remaja Dalam Menjaga Diri Dari Pergaulan Bebas Di SMA N 1 Batang Kuis - Samosir, Yohana; Annisa, Pariqa; Sinaga, Elfalini Warnelis; Hafiiza, Salsabila Ratu; Fitrah, Indah Novia; Manik, Sawilla; Nurqurotul, Anisa; Pulungan, Fifit Novelina; Maharani, Nazli; Tamba, Elisa Vetrawati; Nurmadani, Lifa; Hulu, Milka Septriani (LPPM UMRI, 2025)
Free association or promiscuous behavior is a deviant form of behavior commonly experienced by teenagers and has negative impacts on their health, education, and future. The main causes include environmental influences, lack of sexual education, and weak parental supervision. This community service aimed to increase students’ awareness regarding the risks of free association through health education, discussion, and the distribution of leaflets. The activity was carried out at SMAN 1 Batang Kuis involving 36 eleventh-grade students. The methods used included presentations, interactive discussions, and questionnaires. Results showed that 9 students (25%) had high understanding, 21 students (58.33%) had moderate understanding, and 6 students (16.67%) had low understanding. Most students obtained information from media (77.78%), while only 22.22% relied on non-media sources. The activity successfully increased students’ awareness of free association and encouraged positive behavioral attitudes. Continuous education involving schools, parents, and communities is recommended to prevent deviant behavior in adolescents.